Caenorhabditis elegans Decapping Proteins: Localization and Functional Analysis of Dcp1, Dcp2, and DcpS during Embryogenesis - Lall, Sabbi (The American Society for Cell Biology, 2005)
Though posttranscriptional regulation is important for early embryogenesis, little is understood regarding control of mRNA decay during development. Previous work defined two major pathways by which normal transcripts are degraded in eukaryotes. However it is not known which pathways are key in mRNA decay during early patterning or whether developmental transcripts are turned over via specific pathways. Here we show that Caenorhabditis elegans Dcp2 is localized to distinct foci during embryogenesis, reminiscent of P-bodies, the sites of mRNA degradation in yeast and mammals. However the decapping enzyme of the 3′ to 5′ transcript decay system (DcpS) localizes throughout the cytoplasm, suggesting this degradation pathway is not highly organized. In addition we find that Dcp2 is localized to P-granules, showing that Dcp2 is stored and/or active in these structures. However RNAi of these decapping enzymes has no obvious effect on embryogenesis. In contrast we find that nuclear cap binding proteins (CBP-20 and 80), eIF4G, and PAB-1 are absolutely required for development. Together our data provides further evidence that pathways of general mRNA metabolism can be remarkably organized during development, with two different decapping enzymes localized in distinct cytoplasmic domains.